Variasi Jenis dan Keberadaan Jamur Ektomikoriza di Labanan, Provinsi Kalimantan Timur dan Implikasi terhadap Hutan Alam Dipterokarpa (Variation in Species and Presence of Ectomycorrhizal Fungi in Labanan, East Kalimantan Province and Implications for Dipterocarp Natural Forests) - Karmilasanti Karmilasanti; Nilam Sari; Darwo Darwo; Catur Budi Wiati (Jurnal Penelitian Hutan Tanaman, 2022)
ABSTRACTThe presence of ectomycorrhizal fungi is one indicator that shows a relatively healthy and good forest. However, the conversion of natural forests to other uses will change the microclimate and may have an impact on the loss of ectomycorrhizal fungi. This study aimed to identify the presence of ectomycorrhizal fungi in the Labanan research forest based on the index of abundance, diversity, evenness, dominance, and habitat. The research method used was purposive sampling. The number of plots made was six, with a plot size of 50 x 50 m. The results showed that the variety and presence of ectomycorrhizal fungi in the Labanan research forest were low due to disturbed environmental conditions. This was indicated by low diversity, medium evenness, and moderate species dominance indexes. Therefore, it is necessary to enrich the endemic dipterocarp species that have been associated with local ectomycorrhizal fungi to restore the condition of the dipterocarp forest. The dominant species of discovered ectomycorrhizal fungi were Amanita spreta and Coltricia sp. There were 17 species (70.83%) of ectomycorrhizal fungi encountered in the saprophytic habitat, while seven were discovered in the epiphytic habitat (29.17%).Keywords: Fungi, abundance, diversity, saprophytic, epiphyticABSTRAK Keberadaan jamur ektomikoriza menjadi salah satu indikator yang menunjukkan hutan dalam kondisi baik. Konversi hutan alam menjadi peruntukan lain akan mengubah iklim mikro dan bisa berdampak terhadap hilangnya jamur ektomikoriza. Penelitian bertujuan untuk mengidentifikasi keberadaan jamur ektomikoriza di hutan penelitian Labanan berdasarkan indeks kelimpahan, keanekaragaman, kemerataan, dominansi dan habitatnya. Metode penelitian menggunakan metode purposive sampling.  Jumlah plot dibuat ada 6 plot dengan ukuran plot 50 m x 50 m. Hasil penelitian menunjukkan bahwa variasi jenis dan keberadaan jamur ektomikoriza di hutan penelitian Labanan termasuk rendah dikarenakan kondisi lingkungannya mulai terganggu. Hal ini ditunjukan indeks keanekaragaman rendah, indeks kemerataan sedang, dan indeks dominasi spesies sedang. Untuk memulihkan kondisi hutan dipterokarpa tersebut, maka perlu pengayaan jenis dipterokarpa endemik yang telah berasosiasi dengan jamur ektomikoriza setempat. Jenis jamur ektomikoriza yang dominan adalah Amanita spreta dan Coltricia sp. Pada habitat saprofit terdapat 17 spesies (70,83%) sedangkan pada habitat epifit terdapat 7 spesies (29,17%).Kata kunci: Fungi, kelimpahan, keragaman, saprofit, epifit